A sociological study of school transfer and the learning of mathematics - Noyes, Andrew (2004)
This research explores the complexities of children's everyday experience, examining the common threads and distinctive textures of the lives of four children on their educational journeys from primary to secondary school. Whilst the classroom focus of the empirical work has remained with the teaching and learning of mathematics, I have retained a wider view on the overlapping social spaces in which these children are located. Hence this thesis is less to do with mathematics per se than it is concerned with the lives of children and their families, friends and teachers. This research was conducted, and this thesis constructed, in parallel to my transition into academia and so what follows narrates part of my own story of transfer and socialisation. The notion of reflexivity, of understanding my position within the research, is central to the methodological and theoretical work of the thesis and so I will begin with an account of how I have come to be doing this research, at this time, in this place.